Meatpacking in the COVID-19 context - India Luxton (Journal of Agriculture, Food Systems, and Community Development, 2025)
In January 2020, the coronavirus began spreading rapidly across the United States and became an emergent public health crisis. To mitigate the spread of the virus, state, local, and federal governments implemented various disease mitigation strategies including mask mandates, social distancing requirements, and business closures. However, under the Defense Production Act of 1950, meatpacking plants were designated as essential infrastructure and maintained operation throughout the pandemic. Drawing on 39 in-depth interviews, this article analyzes (1) factors that influenced responses to worker safety during COVID-19 in the meatpacking sector; (2) barriers to disease mitigation and worker justice; and (3) the consequences of industry concentration during an unprecedented public health crisis. Research results show that inadequate safety measures implemented by meatpacking firms, particularly in the early months of the pandemic, when combined with limited federal oversight, contributed significantly to unsafe working conditions and increased risk of disease transmission. These findings highlight the need for reforming worker safety policies, diversification of the sector, and the development of a more robust workers’ compensation system to better protect the health and safety of meatpacking workers.